"Hashtags work everywhere": The pragmatic functions of spoken hashtags. (April 2018) - Scott, Kate
Abstract: Hashtags online perform a range of linguistic (Zappavigna, 2015) and pragmatic (Scott, 2015) functions alongside their categorising and searching functionalities. In Scott (2015), I argued that these different functions are, at least partly, driven by the properties associated with mediated discourse. However, hashtags are also sometimes produced in spoken discourse, where the interlocutors share a physical context and are likely to have access to a range of contextual assumptions and non-verbal cues that are unavailable online. In face-to-face communication the audience is less likely to be "imagined" in the sense ofboyd (2010) and the speaker is less likely to have to negotiate "context collapse", as identified byMarwick and boyd (2011) . Drawing on principles from the relevance-theoretic pragmatic framework (Sperber and Wilson, 1986/95), I argue that in such an enriched context, the range of pragmatic functions of hashtags is likely to be reduced, and will be motivated by factors other than an impoverished discourse context. I draw on data from attested spoken examples and show that spoken hashtags seem to be largely restricted to their interpersonal "metacomment" (Zappavigna, 2015, p. 6) function, and that they are most commonly used to provide evaluative judgements on the rest of the utterance and to guide inferences concerning the speaker's attitudinal stance.